All metrics are equal, but some metrics are more equal than others: A systematic search and review on the use of the term 'metric'. - Núria Duran Adroher; Birgit Prodinger; Carolina Saskia Fellinghauer; Alan Tennant (PLoS ONE, 2018)
Objective To examine the use of the term 'metric' in health and social sciences' literature, focusing on the interval scale implication of the term in Modern Test Theory (MTT). Materials and methods A systematic search and review on MTT studies including 'metric' or 'interval scale' was performed in the health and social sciences literature. The search was restricted to 2001-2005 and 2011-2015. A Text Mining algorithm was employed to operationalize the eligibility criteria and to explore the uses of 'metric'. The paradigm of each included article (Rasch Measurement Theory (RMT), Item Response Theory (IRT) or both), as well as its type (Theoretical, Methodological, Teaching, Application, Miscellaneous) were determined. An inductive thematic analysis on the first three types was performed. Results 70.6% of the 1337 included articles were allocated to RMT, and 68.4% were application papers. Among the number of uses of 'metric', it was predominantly a synonym of 'scale'; as adjective, it referred to measurement or quantification. Three incompatible themes 'only RMT/all MTT/no MTT models can provide interval measures' were identified, but 'interval scale' was considerably more mentioned in RMT than in IRT. Conclusion 'Metric' is used in many different ways, and there is no consensus on which MTT metric has interval scale properties. Nevertheless, when using the term 'metric', the authors should specify the level of the metric being used (ordinal, ordered, interval, ratio), and justify why according to them the metric is at that level.